Castleman’s disease in an HIV-positive patient - Mesía-Angeles, Diego (2023)
A 38-year-old man from Lima, with a history of HIV for three years in treatment, presented with a sensation of thermal elevation, nocturnal diaphoresis and productive cough with whitish expectoration; he also had a pulsating bitemporal headache and, one week before admission, he presented shortness of breath associated with sore throat, dysphonia and oppressive chest pain of intensity 6/10. Due to persistence of symptoms, he went to the Emergency Department, where the chest X-ray showed a mediastinal mass, so it was decided to hospitalize him. Chest TEM showed a left mediastinal mass, with multiple cervical and mediastinal adenopathies; and abdominal TEM showed a mass in the aortic bifurcation and multiple pararaortic and inguinal nodes. Inguinal node biopsyshowed histology compatible with Castleman’s disease. Chemotherapy was started, with favorable evolution and improvement of symptoms.